Evaluation of object-based and ontology-based models in context-aware systems - Anisi, M. H. (IEEE Explorer, 2011)
Today, context-aware systems are discussed as one of the key subjects in ubiquitous computing systems. In this area, researchers have been trying to find some techniques for context information modeling. So that attaining general and efficient model for managing, storing and retrieving data and contextual information is a necessary aspect. In this regard and in order to achieving this goal, several methods already have been proposed. In our research and in this paper, object-based models and ontology-based models are introduced as two most famous models for modeling the context information along with some novel approaches that are based on these models. In continuation, the key requirements of an effective model will be introduced and finally the proposed models will be evaluated as for these requirements.